Evangelism In Muslim And Christian Contexts: A Comparative Study Of Mission Strategies - Fatiu Karatu; Tosin Abolaji (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
The idea of mission is not an exclusive concept and practice of a particular faith. Rather, it is a recognized practice among adherents of various religions, the Muslim and the Christian communities inclusive. The word “evangelism” from the Greek origin evangelion meaning ‘to bring good news’, which has its similitude to “At-Tabsh?r” in the Arabic language. Evangelism is a child of necessity born out of the desire to execute God’s given mandate to the believers. The thrust of this paper is to critically examine evangelism in the Muslim and Christian contexts, with emphasis on the areas of convergence and divergence of mission strategies. The study employed historical, descriptive, and participatory observation methods for data collection. These availed the work the opportunity to trace related historical facts and describe issues as examined, while data were analyzed using a peer-reviewed submission of the authors. It was observed that the use of force in evangelism is unethical, inhumane, and irreligious. Therefore, the study recommended that adherents of both religions (Islam and Christianity) should embrace their similarities in mission and shun religious particularity and exclusivity.